Avaliação do impacto do microcrédito na renda das mulheres microempreendedoras - Lima, Cristiano Queiroz (2025)
This work presents an empirical investigation on the impact of microcredit on the revenue of female entrepreneurs of Centro de Apoio aos Pequenos Empreendimentos do Estado da Bahia (CEAP-BA) in the Feira de Santana-BA unit, as well as interviews obtained through an applied questionnaire. The economic-financial analysis, as well as the qualitative of the data observed in the interviews aim to demonstrate that the impact of microcredit on income generation for female entrepreneurs at CEAPE-BA can be expressive one. The results aim to reveal that female microentrepreneurs in lower-class neighborhoods in Feira de Santana-BA experience a significant impact on their incomes and on the quality of life of their families promoted by microcredit. Microcredit is a tool for social inclusion, providing small credit amounts, making it possible for people to restore their dignity and to promote personal and business development, as well as increase on income and quality of life. Therefore, in the context of the female entrepreneurs, this becomes even more evident, as women have limited opportunities to access microcredit to invest in their businesses. Considering that scenario, the purpose of this work is to assess the type of impact that microcredit has on improving the lives of families and their businesses, especially for women who are great entrepreneurs, but lack support to achieve success. Through this tool (microcredit), it is possible to have a positive impact on income generation and overall improvements in the quality of life for the families of the female microentrepreneurs of CEAPE-BA.